(3GdMQH GdGSJHGbjI aj V`hA GdbGfhf Gd`Ohdj (B/ s - (3GjGO jGSjf MSjf chNIs; (3CMeO CHhGdhaG s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3YGdLJ gPg GdQSGdI ETcGdjI (B"(3GdMQH GdGSJHGbjI aj VhA GdbGfhf GdOhdj(B": (3aLGAJ eJVenqfkI aUdkG JegjOjkG(B: (3Ke HGHjf QFjSjf jMhjGf CQHYI aUhd(B: (3hGSJYQV GdaUd GdJegjOj JGQjN GdMQH GdGSJHGbjI heaghegG GdPj CUHM jTpqcd aj GdhbJ GdQGgf ETcGdjI aj EWGQ GdYdGbGJ GdOhdjI; HSHH YOe JMOjOgG aj fUhU GdbGfhf GdOhdj GdYGe GdeYGUQ(B: (3ajeG Mnqdnd GdHGH GdChd eOi eTQhYjI gPg GdMQH HeG jSGge aj HjGf GdJcjja GdbGfhfj GdUMjM dgG ef NdGd JMOjO GdehGba ef gPg GdMQH aj VhA eUGOQ GdbGfhf GdOhdj (B((3GdeYGgOGJ(B: (3hGdYQa(B: (3hGdabg hGdbVGA(B) (3hcPdc JMOjO ehba GdefXeGJ GdOhdjI (B((3HfhYjgG GdGbdjejI hGdYGdejI(B) (3hOhQgG MjGd eeGQSI gPG GdfeW ef GdMQH(B: (3CeG GdHGH GdKGfj(B: (3abO JVnqef YQVkG dHYV Cge GdeeGQSGJ GdYedjI dgPg GdMQH YHQ JWHjbGJ HYV GdOhd dgG (B((3hNUhUkG ef bHd GdhdGjGJ GdeJMOI GdGeQjcjI hESQGFjd(B)(3; hdCf eeGQSI eKd gPG GdfhY ef GdMQhH KHJJ HGdOdjd GdTQYj (B((3hab eYXe eUGOQ GdbGfhf GdOhdj GdeYGUQ(B: (3hhabkG deG jLQj Ydjg GdYed GdOhdj heeGQSGJ ZGdHjI GdOhd(B) (3CfgG ZjQ eTQhYI(B: (3hYdjg abO JfLe Yf eeGQSJgG BKGQ LGfHjI(B- (3SdHjI Ydi fSb GdYdGbGJ GdOhdjI(B: (3hGdbGfhf GdOhdj(B: (3hHGdJGdj Ydi GdTQYjI GdOhdjI(B: (3hGdfXGe GdOhdj GdYGdej(B: (3eeG jJQnqJH Ydjg fThA GdeSFhdjI GdbGfhfjI GdOhdjI Ydi cd ef jJhnqQW aj eeGQSJgG (B((3ShGA ef WQa GdOhd(B: (3Ch GdCaQGO(B: (3Ch GdefXeGJ GdOhdjI(B)(3; haj GdNJGe CfgjfG GdQSGdI HeHMK CNjQ eMGhdI efG aj GdEdeGe HgPg GdMQH(B: (3heG SJFhd Edjg aj GdeSJbHd ef NdGd EjQGO HYV GdHOGFd GdgGeI(B: (3hGdebJQMGJ GdaqYGdI dehGLgJgG aj VhA CMcGe GdTQYjI GdOhdjI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdis
(3HHdjhLQGajG(B: (3UaMGJ (B459-491s
Keywords: (3GdMQH GdGSJHGbjIs; (3GdYOhGfs; (3GdJONd GdOhdis; (3GdMQH GdhbGFjIs; (3GdMeGjI GdPGJjIs; (3Mb GdOaGY GdTQYi Yf GdfaSs; (3GdOaGY GdhbGFis; (3MGdI GdVQhQIs; (3GdJOGHjQ GdeVGOIs; (3GdGYeGd GdGfJbGejIs; (3GSJQGJjLjJG GdQOY hGdGMJhGAs; (3Mb JbQjQ GdeUjQs; (3fXGe GdGef GdLeGYis; (3eHOC GdJVGef GdOhdis; (3GdeSFhdjI GdOhdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs